ManTool: Application as Manufacturing Tools for Resources Management based on GIS - Ika Arum Puspita (International Journal of Innovation in Enterprise System, 2021)
Competition in the textile industry is very high. Companies must be able to meet market needs by producing goods according to demand. In producing an item, it is necessary to design the amount of raw material required. This study aims to publish geographic information system (GIS) based application design as a tool in resource management. This application is named ManTool. ManTool can provide a reminder when raw material stocks run out. With this system, the company can order raw materials, and the production system continues to run well. This system is designed based on a Geographical Information System (GIS), it is easier for companies to determine which supplier of raw materials to choose. The method of making this system is by using the waterfall method. This method produces the right system because each stage is identified sequentially. The result of this research is a geographic information system-based application. With this application, the company will get a notification when the raw material runs out, and the company will get the right supplier's recommendation to buy raw material.